Analisis Kekuatan Tarik dan Kekasaran Kawat Tembaga Hasil Drawing akibat Variasi Persentase Reduksi - Mohammad Firman; Mahros Darsin; Hari Arbiantara (ROTOR, 2013)
Wire drawing is cold working process to reduce the cross-sectional area. The value of reduction is different in every process, depend on the needs and working parameters. The degree of reduction causes differences of copper wire rod in the characteristics and quality, such as its tensile strength and roughness. The purpose of this research is to determine the influence degree of reduction to the tensile strength and roughness of copper wire. The research method is comparing the tensile strength and roughness of copper wires control with drawed copper wires, without repetition stage. The speciments used in this research are pure copper rods (99.9%) with 3.1 mm, 3.2 mm and 3.25 mm in diameter and 2.8 mm of die output, so will get the degree of reductions are 19%, 23% and 26%. The results of this research was the wire drawing process increase the tensile strength of copper rods from 86.87 MPa to 100.74 MPa on 19% reduction. On 23% reduction the tensile strength increase from 82.24 MPa to 105.62 MPa. The greatest increase of tensile strength was result by 26% reduction, it was from 86.87 MPa to 115.36 MPa With the more of degree of reduction on the drawing process led the increase of tensile strength will be greater. This research also obtained the result that the wire drawing process result the decrease roughness of copper rods from 0,144 μm to 0,089 μm on 19% reduction, from 0.146 μm to 0.087 μm on 23% reduction and the copper rod roughness decrease from 0.159 μm to 0.083 μm on 26% reduction. The increase of degree of reduction produce insignificantly result of surface roughness changing. Keywords: Roughness, Tensile Strength, Wire Drawing, Reduction, Copper